Risk pricing strategies for public-private partnership projects - Boussabaine, Halim A. (Chichester, West Sussex, UK : Wiley-Blackwell, 2013)
"This book sets out the key principle strategies involved in risk pricing of PPP projects in a clear and accessible way and provides the reader with fundamental principles of risk pricing theories and enveloping processes"--
Machine generated contents note: Contents Chapter 1: Mapping of the PPP process. 1.1 Introduction. 1.2 key stages in the PFI/PPP procurement process. 1.3 PPP as a driver for risk transfer for the private sector. 1.4 PPP as a driver for value for money. 1.5 Risk and value for money. 1.7 Summary. 1.8 References. Chapter 2: Project risk management strategies. 2.1 Introduction. 2.1 Types of project risk. 2.3 Project life cycle risk management plan. 2.4 The project risk management process. 2.5 Strategies for project risk management. 2.6 Risk governance. 2.7 Summary. 2.8 References. Chapter 3: Risk management in PPP projects. 3.1 Introduction. 3.2 An integrated framework for risk management of PPP projects. 3.3 Design risk management. 3.4 Construction Risk Management. 3.5 Operation risk management. 3.6 Project finance risk management. 3.7 Summary. 3.8 References. Chapter 4: Project risk measurement and modelling. 4.1 Introduction. 4.2 quantifying risks. 4.3 Risk modelling methods. 4.4 Selecting a risk modelling technique. 4.5 Building risk models. 4.6 Assessing the accuracy of risk models. 6.7 Summary. 6.8 References. Chapter 5: Strategies for risk pricing. 5.1 Introduction. 5.2 Principles of risk pricing strategies. 5.3 Risk pricing management strategies. 5.4 Value gain from risk retention. 5.5 Value loss from risk retention. 5.6 Optimum return on risk retention. 5.7 Cost of risk control. 5.8 Resources capability for risk control. 5.9 Summary. 5.10 References. Chapter 6: Pricing design risks. 6.1 Introduction. 6.2 Overview of design risks. 6.3 Strategies for mitigating and managing design risks. 6.4 Pricing design risks. 6.5 Design risks pricing example. 6.6 Summary. 6.7 References. Chapter 7: Pricing construction risks. 7.1 Introduction. 7.2 Overview of construction risks. 7.3 Strategies for mitigating and managing construction risks. 7.4 Pricing construction risks. 7.5 Construction risks pricing example. 7.6 Summary. 7.7 References. Chapter 8: Pricing operational risks. 8.1 Introduction. 8.2 Overview of operational risks. 8.3 Strategies for mitigating and managing operational design risks. 8.4 Pricing operational risks. 8.5 Operational risks pricing example. 8.6 Summary. 8.7 References. Chapter 9: Pricing project finance risks. 9.1 Introduction. 9.2 Overview of project finance. 9.3 Project finance risk map. 9.4 Strategies for pricing project finance risks. 9.5 Project finance risk price modelling. 9.6 Summary. 9.7 References.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Public-private sector cooperation; Risk management; Building -- Estimates; TECHNOLOGY & ENGINEERING / Civil / General; Building -- Estimates; Public-private sector cooperation; Risk management; Electronic books; Electronic books